Islam Law Review About Applications of Contraception Vasetomy and Tubectomy Methods to Muslim Community in West Sumatera - Dasrizal Dahlan; Jusmawati Jusmawati (Alhurriyah, 2022)
The population of Indonesia, the majority of whom are Muslims, automatically become participants in the Family Planning Program. The Family Planning Program has offered various contraceptives, some of which are allowed to be used by Muslims and those that are not. Contraceptive devices for Muslim women are IUD, Pills, Injectable Drugs, Implants, and other traditional methods, while those that are not allowed for Muslim women are Menstrual Regulation, Abortion, Ligasituba which binds the oviduct sac, and tubectomy, namely lifting the ovum place called the sterilization. Men can use condoms and vasectomy. Sterilization for both men (vasectomy) and women (Tubectomy) according to Islam is haram (forbidden) because it causes permanent infertility. Sterilization can be done if the family planning participant is at risk if using other contraceptive methods or other contraceptive methods fail to regulate birth. Based on the problems above, this study wants to reveal how the application of contraception devices for vasectomy and tubectomy by acceptors to the Muslim community of West Sumatra. Data was collected using documentation and interview techniques, while data analysis was carried out using qualitative descriptive techniques. The results of the study revealed that the use of vasectomy and tubectomy contraceptives was generally based on considerations of the wife's health and adjusted to the doctor's recommendations.Penduduk Indonesia mayoritas beragama Islam dengan sendirinya menjadi peserta program Keluarga Berencana Program Keluarga Berencana telah menawarkan bermacam-macam alat kontrasepsi, yang boleh dipakai oleh umat Islam ada pula yang tidak boleh. Alat kontrasepsi untuk wanita Islam adalah, IUD, Pil, Obat Suntik, Susuk dan cara-cara tradisional lainnya, sedangkan yang tidak boleh untuk wanita Islam adalah Menstrual Regulation, Abortus, Ligasituba yang mengikat saluran kantong ovum dan tubektomi yakni mengangkat tempat ovum yang disebut dengan sterilisasi. Laki-laki dapat memakai kontap kondom dan vasektomi. Sterilisasi baik untuk laki-laki (Vasektomi) maupun untuk wanita (Tubektomi) menurut Islam pada dasarnya haram (dilarang) karena mengakibatkan kemandulan yang tetap. Sterilisasi dapat dilakukan jika peserta KB beresiko jika memakai alat kontrasepsi lainnya atau alat kontrasepsi lain itu gagal mengatur kelahiran. Berdasarkan permasalahan di atas maka penelitian ini ingin mengungkap bagaimana penerapan alat kontrasepsi KB Vasektomi dan Tubektomi oleh aseptor pada komunitas Muslim Sumatera Barat.  Pengumpulan data dilakukan dengan teknik dokumentasi dan wawancara, sedangkan analisis data dilakukan dengan teknik deskriptif kualitatif. Hasil penelitian mengungkapkan bahwa pemakaian alat kontrasepsi vasektomi dan tubektomi secara umum didasarkan pada pertimbangan kesehatan istri dan disesuaikan dengan rekomendasi dokter.